Taekwondo kicks at the center of biomechanical research: A systematic review - Aybüke Yilmaz, E.; Ates, O. (Kinesiology, 2025)
Taekwondo is an Olympic martial art that emphasizes complex kicking techniques requiring meticulous biomechanical execution. Understanding the mechanical determinants of these kicks is essential for performance enhancement and injury prevention. This systematic review aims at combining the available literature on the kinematic and kinetic features of taekwondo kicks to understand the biomechanics of the technique and training implications. A comprehensive search was done in the PubMed, Scopus, and Web of Science databases following PRISMA 2020 guidelines. The studies included used experimental methods, were published in scientific peer-reviewed journals and focused on the biomechanics of taekwondo kicks from the post-1996 period. A total of 294 articles were identified, and 86 studies met the inclusion criteria. The analysis revealed four main themes: dollyo chagi (n=49), ap chagi (n=9), yeop chagi (n=4), multiple kicks (n=12) and other kicks (n=12). The most consistent determinants of performance were hip joint torque and ground reaction forces (kinetics), and distal segment velocity (kinematics). Dollyo chagi had the highest rotational dynamics, necessitating power and speed, while yeop chagi showed how mass can be efficiently utilized to produce force. Ap chagi used a proximal-to-distal energy transfer mechanism to achieve the most efficient energy transfer. This review confirms the importance of biomechanics in the execution of taekwondo kicking techniques. It determines energy transfer, joint coordination, and muscle activation as crucial factors that describe the performance. Coaches should focus on hip mobility drills and proximal-todistal sequencing exercises to enhance power output while minimizing joint loading to reduce injury risks.